Internalization of Moderation Values Through Citizenship Education At University - Agustan, Agustan; Zurahmah, Zurahmah; Sabaruddin, Sabaruddin; Laman, Ilham; Nawawi, Muhammad Fiqhri (Palita: Journal of Social Religion Research, 2024)
This article aims to examine the internalization of the value of religious moderation through Citizenship Education in Higher Education. This research uses a qualitative approach with the type of library research, where the data comes from books, articles and other sources that are relevant to the problem formulation. The results of the research show that: first, the internalization of the values of religious moderation in Citizenship Education in Higher Education is carried out through: (a) the existence of Citizenship Education courses, which are substantially related directly to the formation of moderate students character, (b) the example set by lecturers Citizenship Education which always prioritizes a moderate attitude, and (c) the methods used in teaching Citizenship Education. Second, the implementation of religious moderation in Citizenship Education in Higher Education is carried out based on: (a) national commitment, (b) tolerance, (c) non-violence, and (d) accommodating to local culture.